Spirit wolf - Lasky, Kathryn (Lasky, Kathryn. Wolves of the Beyond, 2013)
When earthquakes and erupting volcanoes strike the Beyond, Faolan and the other surviving wolves must head for the Distant Blue, where they hope to find a new home.